New Plasmid Tools for Genetic Analysis of Actinobacillus pleuropneumoniae and Other Pasteurellaceae - Bossé,JT; Durham,AL; Rycroft,AN; Kroll,JS; Langford,PR (2009)
We have generated a set of plasmids, based on the mobilizable shuttle vector pMIDG100, which can be used as tools for genetic manipulation of Actinobacillus pleuropneumoniae and other members of the Pasteurellaceae. A tandem reporter plasmid, pMC-Tandem, carrying promoterless xylE and gfpmut3 genes downstream of a multiple-cloning site (MCS), can be used for identification of transcriptional regulators and conditions which favor gene expression from different cloned promoters. The ability to detect transcriptional regulators using the tandem reporter system was validated in A. pleuropneumoniae using the cloned rpoE (σE) promoter (P). The resulting plasmid, pMCrpoEP, was used to identify a mutant defective in production of RseA, the negative regulator of σE, among a bank of random transposon mutants, as well as to detect induction of σE following exposure of A. pleuropneumoniae to ethanol or heat shock. pMCsodCP, carrying the cloned sodC promoter of A. pleuropneumoniae, was functional in A. pleuropneumoniae, Haemophilus influenzae, Haemophilus parasuis, Mannheimia haemolytica, and Pasteurella multocida. Two general expression vectors, pMK-Express and pMC-Express, which differ in their antibiotic resistance markers (kanamycin and chloramphenicol, respectively), were constructed for the Pasteurellaceae. Both plasmids have the A. pleuropneumoniae sodC promoter upstream of the gfpmut3 gene and an extended MCS. Replacement of gfpmut3 with a gene of interest allows complementation and heterologous gene expression, as evidenced by expression of the Haemophilus ducreyi nadV gene in A. pleuropneumoniae, rendering the latter NAD independent.